Bank Debt, Mutual Fund Equity, and Swing Pricing in Liquidity Provision - Ma, Yiming; Xiao, Kairong; Zeng, Yao (Review of Financial Studies, 2025)
Abstract Liquidity provision is often attributed to debt-issuing intermediaries like banks. We develop a unified theoretical framework and empirically show that mutual funds issuing demandable equity also provide an economically significant amount of liquidity by insuring against idiosyncratic liquidity shocks. Quantitatively, bond funds provide 12.5% of the liquidity that banks provide per dollar. Our model further shows that when equity values incorporate the liquidation cost from redemptions, as in swing pricing, liquidity provision is not necessarily reduced. This is because swing pricing may increase funds’ capacity for holding illiquid assets without inducing panic runs.